UPAYA PERLINDUNGAN HUKUM BAGI ANAK PADA SATUAN RESERSE KRIMINAL KEPOLISIAN RESORT SINTANG - Abang Zainudin; Siharnain Aloysius (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
As a state apparatus that plays a role in maintaining public security and order, enforcing the law, and providing protection, shelter, and services to the community in order to maintain security in the jurisdiction of the Sintang Police Resort (Polres), the Sintang Police through the Women and Children Protection Unit of the Sintang Police Criminal Investigation Unit is obliged to provide legal protection for children. Efforts to protect children legally at the Sintang Police Criminal Investigation Unit are carried out through socialization and coordination with related agencies. Success in raising legal awareness of legal protection for children to the community requires an effective socialization strategy. As an agent that actively promotes legal protection for children, the PPA Unit of the Sintang Police Criminal Investigation Unit must have important resources in order to carry out its functions properly. These resources include: human resources, facilities and infrastructure along with budget. The conclusion of this study is that efforts to raise legal awareness of child protection for the community in the jurisdiction of the Sintang Police are still not optimal. Therefore, it is recommended that the quality and quantity of socialization be improved, both in terms of frequency and target coverage by improving the coordination function between related agencies. Furthermore, the PPA Unit of the Sintang Police Criminal Investigation Unit needs to have a special budget for outreach and socialization programs in order to build public legal awareness so that legal protection efforts for children do not only depend on initiatives from agencies outside the Police.